Generalized iteration method for the solution of fourth order BVP via Green's function - Akgun, Fatma Aydin; Rasulov, Zaur (NEW YORK BUSINESS GLOBAL LLC, 2021)
The aim of this paper is to extend and generalize Picard-Green's fixed point iteration method for the solution of fourth-order Boundary Value Problems. Several numerical applications to linear and nonlinear fourth-order Boundary Value Problems are discussed to illustrate the main results.
Keywords: Boundary value problem; fixed point iteration method; Green's function; integral operator; rate of convergence; EXISTENCE; EQUATIONS; Mathematics